In light of interdisciplinary studies: a study on issues in sociolinguistics and its relationship to linguistics and sociology - kedideh, abdelmadjid (El Omda in Linguistics and Discourse Analysis, 2023)
:Abstract Sociolinguistics is only consistent with the integration of sociology with linguistics as two aspects of one flag. This science has become the focus of modern linguistic studies, which have shifted from theoretical to psychological/social linguistic studies with excellence; It has become concerned with the study of language and its relationship with the individual and society, to examine factors affecting it during use according to its social context; Language problems are also addressed, such as language duplication and language conflict… etc. They are one of the most important areas of research; which I am analyzing in this paper; looking for the most important distinctions of the approaches raised in this area.